Mediação cultural em museus e exposições de história: conversas sobre imagens/história e suas interpretações - Alencar, Valéria Peixoto de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This doctoral research project in Arts started in 2011 at Instituto de Artes/UNESP, entitled Cultural mediation in history museums and exhibitions. Conversations about images / history and their interpretation, under the guidance of Professor Dr. Rejane Coutinho, and it was built on the assumption that the exhibition discourse created in the history museums since the nineteenth century in order to build a national memory from the use of a visuality, is still present and reverberates in cultural mediation work, either reproducing or criticizing such visuality. Field research was conducted at Museu Paulista in 2012 and it included documentation from the analysis regarding the Taunay management as well as the observation of educational work; also in 2013/2014 a research was carried out in London during my doctoral exchange program. The research resulted in two field diaries that were important source of data and reflections. The thesis begins with a contextualization of the emergence of the National History Museums (turn of the eighteenth to the nineteenth century), the discussion of the relation between images and history and of concepts such as representation and visuality. It also shows the relation picture / history with regard to the pedagogical use of the image from the same time frame of the emergence of the National History Museums until the present day, focusing on the intuitive method of teaching (the lessons of things), on the methodology of heritage education and the one of education proposed as mediation. Finally, it presents the mediation work of the educators of Museu Paulista, especially in the exhibition designed by Affonso Taunay for the centenary of Brazil‟s Independence, and proposes an exercise in contextualization, analysis and imagination of the cultural mediation work that discusses the concepts of dissent (RANCIÈRE), symptom (DIDI-HUBERMAN), countervisuality (MIRZOEFF) ...

Esta pesquisa de Doutorado em Artes iniciada em 2011 no Instituto de Artes da UNESP, intitulada Mediação cultural em museus e exposições de história. Conversas sobre imagens/história e suas interpretações, sob a orientação da Profa. Dra. Rejane Coutinho, foi construída a partir da hipótese de que o discurso expositivo criado nos museus de história desde o século XIX, para construir uma memória nacional a partir da utilização de uma visualidade, ainda se faz presente e reverbera no trabalho de mediação cultural, reproduzindo ou criticando tal visualidade. Foi realizada pesquisa de campo no Museu Paulista no ano de 2012 que englobou desde a análise de documentação referente à gestão Taunay bem como a observação do trabalho educativo; também em 2013/2014 foi realizada pesquisa em Londres durante o período do Doutorado sanduíche, tais momentos resultaram em dois diários de campo que foram importante fonte de dados e reflexões. A tese inicia com uma contextualização do surgimento dos Museus de História Nacionais (virada dos séculos XVIII/XIX), da discussão da relação entre imagens e história e de conceitos como representação e visualidade. Também apresenta a relação imagem/história no que se refere ao uso pedagógico da imagem a partir do mesmo recorte temporal do surgimento dos Museus Nacionais de História até os dias atuais, enfocando no método intuitivo de ensino (as lições de coisas), na metodologia da Educação Patrimonial e na proposta da educação como mediação. Por fim, apresenta o trabalho de mediação realizado pelos educadores do Museu Paulista, especialmente na exposição concebida por Affonso Taunay para o centenário da Independência do Brasil, e, propõe um exercício de contextualização, análise e imaginação do dito trabalho de mediação cultural que procura discutir os conceitos de dissenso (RANCIÈRE),...
Keywords: Museus - Aspectos educacionais; Arte e educação; Mediação; Patrimônio cultural; Museums - Educational aspects